Comparison of Online Transportation Regulatory Framework in Indonesia and Several ASEAN Member States - Desril, Raja; Rachman, Miftahur; Santoso, Mulia Akbar (Faculty of Law, Universitas Pekalongan, 2024)
This research is motivated by the need to adjust online transportation regulations in Indonesia with technological developments and rapidly changing societal dynamics. The main issue raised is how the regulatory framework of online transportation in Indonesia is and how it compares to several ASEAN member countries. The discussion shows that regulations in Indonesia still use a conventional approach that is less adaptive to online transportation innovation, often causing legal vacuums and uncertainty for stakeholders. The conclusion of this study states that existing regulations need to be updated to be more comprehensive and responsive to changes. The advice given is that the government should adopt best practices from other ASEAN countries to create more effective regulations, including paying attention to fairness, safety, and welfare aspects for both users and service providers.